Carbon-nanotube-based electrically-short resonant antennas - Franck, Pierre (2014)
We present a study on using carbon nanotubes (CNTs) as the radiating part of resonant antennas in order to reduce their dimensions. A mesoscopic electromagnetic (EM) model for CNTs was developed to allow the simulation of RF devices in classical EM solvers while retaining the specific properties of CNTs. A circuit approach is also used to provide a physical interpretation of the results on monopole antennas and trend prediction. These techniques constitute a platform to study the trends and trade-offs involved in the design of these antennas. Finally, these results are used to assess suitable fabrication techniques for CNT-based short resonant antennas and conclusions are drawn on their potential applications.